On binary features in the evolution of human language - Toyota, Junichi (Theoria et Historia Scientiarum, 2012)
This paper has argued that the binary pair is a powerful feature in both the evolution and the recent historical change of language. It is indeed true that our language requires nouns and verbs to form predicates and to fully meet our daily communicative needs. It is easier for us to consider from our modern perspective that almost all modern languages have more than noun and verb in their lexical categories. However, it has been argued in this paper that this current state of grammar is all due to the emergence of verb. Once there is a noun-verb opposition, it is easy to develop complex grammatical systems through grammaticalisation, as schematically represented in Figure 1. The importance of binary oppositions is not restricted to evolution, but recent historical changes also suggest the importance of binary pairs, possibly recapitulating earlier evolutionary changes of languages. This line of argument would suggest that there can be two stages in linguistic evolution, i.e. the pre-binary stage and the post-binary stage. The pivotal change here is, needless to say, the emergence of verb. Grammaticalisation can easily explain how noun and verb can turn into more complex grammatical structures, i.e. the post-binary stage, but the applicability of grammaticalisation to the pre-binary stage is open to question for the moment. What is important is that our language has spent so much time to come up with the basic binary pair noun and verb, and once there is one, the rest of the development is very easy. This indicates how powerful binary pairs can be.